The Politics of Canadian Broadcasting - Frank W. Peers7 (University of Toronto Press, 2011)
THIS VOLUME traces the development of broadcasting policy in Canada up to the inception of television in 1952. In writing it I have benefited greatly from access to collections of papers and documents, particularly the Alan Flaunt Papers in the Library of the University of British Columbia. Alan Flaunt and Graham Spry were the founders of the Canadian Radio League, and their efforts, more than any other single force, helped transform Canadian broadcasting in the 1930s from a feeble replica of American radio into a system that would meet the interests and needs of Canadians within the two main language groups. I am grateful to Mrs. H. A. Dyde for permission to consult the Flaunt Papers, and to Graham Spry not only for access to his personal collection but for many hours of conversation that helped place the events of those years in perspective. Dr. Gertrude Gunn, of the Harriet Irving Library at the University of New Brunswick, gave me permission to consult the R. B. Bennett Papers then on loan to the Public Archives in Ottawa. The late Austin Weir, himself a pioneer in good broadcasting, was most helpful in discussing broadcasting past and present. Among other former colleagues who assisted me in gathering information were Louise Simard, Margaret Cooke, Davidson Dunton, Rene Landry, Barry MacDonald, Dan McArthur, Neil Morrison, Finlay Payne, and Bernard Trotter. The staff of the Public Archives and the Parliamentary Library in Ottawa were at all times indefatigable in answering my requests. A special word of thanks should go to Professor Alexander Brady, who encouraged me to undertake the study and who has read the greater part of the manuscript, as has Vincent Tovell, a friend and former colleague in the CBC. The research was facilitated by a Canada Council fellowship and by smaller grants from the Centennial Commission and the University of Toronto; the publication was assisted by a grant from the Publications Fund of the University of Toronto Press. For all of these I am most grateful.